End of Capitalism, End of Humanity? - Žižek, Slavoj (Stasis, 2017)
The emergence of biogenetics and the digitalization of our daily lives is an explosive combination, but are the latest tendencies of global capitalism really announcing a new era in which not only the market economy but also the very notion of being-human will be rendered obsolete? Should we celebrate these tendencies as a prospect of radical emancipation, or are they harbingers of a society in which humans will be reduced to cogs in a digital machine? This text tries to move beyond such simple alternatives by way of raising more basic questions: What do we mean by “human” when we speak of posthumanity? Is the vision of posthumanity a realistic prospect or an ideological dream? How can we think about today’s postcapitalist forms of domination?